Evaluation of isolated DCDC converter topologies for future HVDC aerospace microgrids - Tarisciotti, Luca; Costabeber, Alessando; Linglin, Chen; Walker, Adam; Galea, Mikiel (2017)
High performance power conversion equipment is currently gaining an increasing interest for aircraft applications. In particular, isolated bidirectional DC/DC converters are often proposed for modern HVDC aircraft distribution systems. For such reason an evaluation of several isolated DC/DC converter topology is carried out considering the proposed application, interfacing a 270V DC network with a 28V DC network. A trade off evaluation has been carried out for three different topologies and an experimental prototype has been manufactured for the selected conversion architecture. Simulation and experimental results are provided in order to validate the trade off and the design of the proposed converter.